Biological Effects of Medicinal Plants on Induced Periodontitis: A Systematic Review - Jefferson Soares de Oliveira; Moara e Silva Conceição Pinto; Lucas de Araújo de Bastos Santana; Antonione Santos Bezerra Pinto; David di Lenardo; Daniel Fernando Pereira Vasconcelos (International Journal of Dentistry)
Objective. The aim of this systematic review was to investigate the advances in the study of medicinal plants and their biologic effects on periodontitis in animal models. Study Design. A systematic search was conducted by three independent researchers, who screened articles published up to March/2016, to identify the studies that contained sufficient and clear information on the association of the medicinal plants and periodontitis in murine models. The searches were performed using PubMed, Cochrane, and Science Direct databases. Results. After a critical analysis of titles and abstracts, 30 studies were finally eligible for analysis. The studies presented a great diversity of the experiment designed regarding the methods of induced periodontitis and the evaluation of the medicinal plants efficacy. None of the studies described the possible toxic effects associated with the administration of the plant material to animals and whether they could prevent damage to organs caused by systemic effect of induced periodontitis. Gel-based formulations containing plant substances are seen as an interesting strategy to treat periodontitis. Conclusions. In this systematic review, the state-of-the-art knowledge on the medicinal plants and the induced periodontitis was critically evaluated and discussed from the experiment designed to the possible clinical application.